Requirement of the Ca2+ channel β2 subunit for sympathetic PKA phosphorylation - Manabu Murakami; Feng Xu; Takayoshi Ohba; Takeshi Kobayashi; Yoshiro Inoue; Agnieszka M. Murakami; Ichiro Miyoshi; Kyoichi Ono; Noritsugu Tohse (Elsevier, 2021)
Facilitation of cardiac function in response to signals from the sympathetic nervous system is initiated by the phosphorylation of L-type voltage-dependent Ca2+ channels (VDCCs) by protein kinase A (PKA), which in turn is activated by β-adrenoceptors. Among the five subunits (α1, β, α2/δ, and γ) of VDCCs, the α1 subunit and the family of β subunits are substrates for PKA-catalyzed phosphorylation; however, the subunit responsible for β-adrenergic augmentation of Ca2+ channel function has yet to be specifically identified. Here we show that the VDCC β2 subunit is required for PKA phosphorylation upon sympathetic acceleration. In mice with β2 subunit-null mutations, cardiac muscle contraction in response to isoproterenol was reduced and there was no significant increase in Ca2+ channel currents upon PKA-dependent phosphorylation. These findings indicate that within the sympathetic nervous system the β2 subunit of VDCCs is required for physiological PKA-dependent channel phosphorylation.